Stress level affects health and academic performance of undergraduate students in health sciences area courses (Research, Society and Development, 2022)
University students represent a group that is at high risk of stress and even suicide. The present study aimed to investigate the profiles and stress levels of undergraduate students enrolled in health sciences courses at a Brazilian university, and how their health and academic performance are affected. A total of 431 students participated, of which 30% were not stressed, 2.5% were in the alert phase, 38.7% were in the resistance phase, and 28.8% were almost exhausted. Stress levels were related to gender (p = 0.0005), course (p = 0.004), and semester; higher levels of stress negatively influenced students’ academic performance (p = 0.019), socialization (p = 0.020), relationship with the university (p = 0.019), learning (p < 0.0001), sleep (p < 0.0001), and perceived health (p < 0.001). The present study provides evidence regarding the stress levels of health sciences undergraduate students in Brazil, as well as its negative effect on health status and academic performance. It is suggested that further studies should be conducted specially to investigating strategies for students’ stress control in the university environment.